Human resource forecasting and planning - Flores, Marivic Francisco (OBE (Outcome-based education) Approach, 2016)
"The aim of this book is to equipped young professionals and current practitioners in the field of HR Forecasting and Planning on the premise that the modern manager's job is becoming extremely intricate."--Preface